0033 Dysregulated sleep and NREM sleep electroencephalogram delta power induced by intermittent hypoxia exposure are attenuated in NLRP3 knockout mice. (25th May 2022) - Zielinski, Mark; Strecker, Robert; McKenna, James; McNally, James; Cade, Brian; Redline, Susan
Abstract: Introduction: The nucleotide-binding domain leucine rich family pyrin containing 3 (NLRP3) inflammasome protein complex activates caspase-1 to convert the pro-forms of IL-18 and IL-1 beta (IL-1β) into their active forms and is involved in homeostatic sleep and sleep responses to pathogenic stimuli. Intermittent hypoxia (IH) is a hallmark of sleep disordered breathing (SDB) and both IL-18 receptors are associated with SDB in humans. Thus, we hypothesized that NLRP3 inflammasomes are involved in SDB-related sleep disturbances. Methods: Sleep architecture was assessed by polysomnography in NLRP3 knockout (KO) and wild-type (WT) mice (N = 8 per group). A gas exchange mixer delivered house air serving as a control or chronic IH that involved 90 second episodic oxygen reductions that consisted of ambient oxygen (21%) with brief hypoxic conditions ( 10%) that lasted for 3 seconds for the first 10 h of the light period for 5 consecutive days. Gene expression and protein levels in the brain and lungs were assayed using real-time polymerase chain reaction and enzyme-linked immunosorbent assays, respectively. Results: In WT mice, significant increased non-rapid-eye movement (NREM) sleep amounts and NREM sleep electroencephalogram delta power (0.5-4 Hz) were found after 1 day of IH compared to control conditions (p < 0.001). After 5 days of IH, WT mice showed a significant attenuation in NREM sleep amounts and NREM sleep delta power (p < 0.001) and increased wake bout frequency (p = 0.006) when compared to control conditions. However, the IH-induced NREM sleep and NREM sleep delta power enhancements and reductions were attenuated (21-35%) in NLRP3 KO mice compared to WT mice. In WT mice, NLRP3, IL-1β, IL-18 and caspase-1 gene expression, IL-1β and IL-18 protein levels, and caspase-1 activity were significantly increased in the somatosensory cortices, NTS, and lungs after both 1 and 5 days of IH when compared to control conditions (p < 0.05 for all), although NLRP3 KO mice did not exhibit significant differences in molecules downstream of NLRP3 inflammasome activation. Conclusion: Our findings indicate that altered NLRP3 inflammasome activation contributes to dysregulated sleep occurring from IH and likely is involved in sleep disturbances in SDB. Support (If Any): VA Career Development Aware IBX002823, VA Merit BX004500, NIH/NIMH 1R21MH125242, NIH/NHLBI R03 HL154284, and NIH/NHLBI R35 HL135818. JTM received partial salary compensation and funding from Merck Investigator Sponsored Programs but has no conflict of interest with this work.